Preoperative Statin Therapy for Atrial Fibrillation and Renal Failure after Cardiac Surgery - Kuhn, Elmar W.; Liakopoulos, Oliver J.; Choi, Yeong-Hoon; Rahmanian, Parwis; Eghbalzadeh, Kaveh; Slottosch, Ingo; Deppe, Antje Christin; Wahlers, Thorsten C.W. (The Thoracic and Cardiovascular Surgeon, 2020)
Background Performing cardiac surgery in patients with cardiovascular risk factors incorporates a steady risk for the development of postoperative complications. Perioperative statin intake was associated with an improvement of perioperative outcomes in these patients. However, the European Association for Cardio-Thoracic Surgery guidelines regarding the perioperative statin treatment were changed recently due to large studies reporting about relevant adverse effects related to statin therapy.Methods All relevant databases were searched including the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, and the metaRegister of Controlled Trials. Various registries were screened (National Research Register, the ClinicalTrials.gov, and gray literature) with search on online conference indices of relevant scientific meetings. No language restrictions were applied.Results We identified 10 randomized controlled studies summarizing 3,468 participants undergoing various kinds of cardiac surgical procedures. All included studies presented with marked differences regarding study design. Pooled analysis indicated that statin pretreatment was associated with a formally reduced incidence of postoperative atrial fibrillation (AF) (odds ratio [OR] 0.63, 95% confidence interval [CI] 0.39–1.00; p = 0.05) but with an increased incidence of renal failure (OR 1.20, 95% CI 1.01–1.44; p = 0.04) compared with control. Substantial heterogeneity was observed among studies reporting about AF.Conclusion Current but sparse evidence reveals that statin pretreatment is associated with a higher rate of postoperative renal failure compared with control therapy but is ineffective to substantially reduce postoperative AF. Given the relevant heterogeneity among included studies, statin pretreatment cannot be generally recommended.
Keywords: cardiac surgery; statin therapy; adverse outcomes; systematic review; meta-analysis